ENTREPRENEURSHIP FOR YOUNG PEOPLE TO FIND JOBS AND OVERCOME UNEMPLOYMENT PROBLEMS WITH SOCIAL MEDIA - Nst, Asrindah; Purba, Budiman (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
There is a significant need for his employment market among the younger generation, who have transitioned from high school to college. as a result of the fact that a significant number of young individuals are currently seeking employment opportunities through various sources, including newspapers, news, acquaintances, and social media.  There is a wide range of employment opportunities and comprising knowledge, creativity, innovation, soft skills, and hard skills that are possessed by youthful individuals.  Therefore, the future young generation will persist in their creative endeavours by establishing employment opportunities on social media platforms, including being a blogger, content creator, startup, social media administrator, content writer, online animation maker, shopee, lazada, gopay, funds, and traveloka. This will enable the younger generation to secure decent jobs and combat the widespread unemployment that is prevalent in both domestic and international settings.